Development of E-Book Based Instructional Design PjBL Model Integrated Science Literacy To Improve Critical Thinking Abilit - Nursamsu Nursamsu; Siska Rita Mahyuny; Rizky Nafaida; Salwa Rezeqi (Postgraduate, University of Mataram, 2023)
The aim of the research is to develop e-books based on PjBL model instructional design integrated with scientific literacy to improve students' critical thinking skills. To find out the feasibility validation test of e-books based on the instructional design of the PjBL model integrated with scientific literacy. To find out the E-book Effectiveness test on Critical Thinking Ability. The method to be used in this research is to use the research and development (R&D) method. The research stages are determining the material, preliminary research, analysis, design creation, material creation, initial product development, valid, feasibility test, valid, practicality test. The research data is in the form of feasibility test data by validators and the effectiveness of E-books. In critical thinking skills, the research results show that the feasibility test obtained from validation by material experts and biology teachers is reviewed based on presentation, content and language components obtained an average value of due diligence of 92.50% which is in the category very feasible to use. Meanwhile, the results of the N-gain test on the level of students' thinking abilities after using this e-book obtained a score of 0.80% in the good category in improving critical thinking abilities